Differences in Learning Outcomes Between Students Tested in Written Tests and Oral Tests in Economics Subjects - Puspita, Yuni; Ahmad, Syarwani; Nurlina, Nurlina (Universitas Negeri Semarang, 2022)
This study aimed to determine the results of differences in learning outcomes between students who were given a written test and an oral test on economics subjects. The population in this study were all students of class X IPS, which amounted to 97 students. The sampling technique in this study used random sampling. Data collection methods used documentation and tests. The results of this research for class X IPS 1 showed that the average score of the written test results was 80-86, totaling 6 people or 18.75% of the students who took the test, and were categorized as very good. 12 students who scored 66-79 or 37.5% were categorized as good. 6 students who scored 59-65 or 18.75% were categorized as sufficient while students who got a score of 45-58 were 8 people or 24.98% were categorized as poor while in class X IPS2 students who got a score of 66-79 totaling 11 people or 34.40% were categorized as good while students who scored 59-65 totaling 11 people or 34.40% were categorized as good enough. 10 students who got a score of 40-53 or 31.20% were categorized as less good.